Analisis Keterkaitan Antara Aktualisasi Diri dan Kecemasan pada Perempuan Dewasa Awal Korban KDRT di Masa Kecil - Alfahis, Fadhilah Umaira; Soetikno, Naomi (IAIN Syekh Nurjati Cirebon, 2023)
Domestic violence (DV) is one of the most prevalent forms of violence. It not only affects adults but also puts children at risk of becoming victims of DV. Experiencing or witnessing DV in childhood can cause short-term and long-term psychological impacts. One of the long-term effects is the development of an anxious personality in adulthood. As individuals grow, they need to fulfill specific needs to achieve self-actualization, including safety needs. If an individual easily experiences anxiety in adulthood, it is likely that their sense of security is threatened. Thus, anxiety is predicted to be related to self-actualization. This quantitative research aims to investigate the relationship between self-actualization and anxiety levels in early adult women who were victims of DV in childhood. The findings indicate a negative correlation between self-actualization and anxiety in early adult women who experienced DV in childhood.